Manhaj Tarbiyyah al-Aulād fī Sūrah Luqmān - Ritonga, Nur'ainun; Musthofa, Tulus; Haq, Samsul; Wiliani, Wiliani (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research aims to examine the curriculum of child education, specifically focusing on objectives, materials, methods, and media as outlined in Surah Luqman, verses 13 to 20. It is a library-based study employing a qualitative descriptive approach. The primary source for this research is Surah Luqman, verses 13 to 20, while secondary sources include books, studies, and scholarly articles relevant to the topic. Data was collected through documentation, and content analysis was applied to interpret the data based on its content. The findings indicate that the methods of child education in Surah Luqman verses 13 to 20 can be summarized as follows: Educational Objectives: These are categorized into doctrinal objectives, moral objectives, and worship objectives. Educational Materials: These include monotheism (the oneness of God), belief in the Day of Judgment, the beautiful names of God (Asmaul Husna), God's power, commendable morals, reprehensible morals, ethics of debate, and prayer. Educational Methods: These include advice, exemplary modeling, dialogue, repetition, and storytelling. Educational Media: This includes natural elements such as clouds, rain, snow, and ice in the sky, as well as solid dwellings, rivers, trees, plants, and fruits on earth.